Ecological characteristics of pine processionary moth Thaumetopoea pityocampa (Lepidoptera: Notodontidae) larval nests in pine and cedar forests of Algeria - KHALED BOUZAR-ESSAIDI; NOUREDDINE RAHIM; BADREDDINE MEFTAHI; LEILA BENFEKIH (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Bouzar-Essaidi K, Rahim N, Meftahi B, Benfekih L. 2023. Ecological characteristics of pine processionary moth Thaumetopoea pityocampa (Lepidoptera: Notodontidae) larval nests in pine and cedar forests of Algeria. Biodiversitas 24: 2107-2113. The pine processionary moth Thaumetopoea pityocampa) (Lepidoptera: Notodontidae) is one of the most serious pests of pine and cedar forests in Southern Europe and North Africa. In northern Algeria, outbreaks occur in the Aleppo pine (Pinus halepensis) forest, particularly in the semi-arid area and in the Atlas cedar forest (Cedrus atlantica) in the sub-humid elevation area. Under temperate and mountainous climates, the gregarious larvae of this winter-developing insect progressively build a large white, silky nest as a protective shelter during the winter period. We investigated the presence of nests and the environmental parameters (altitude, exposition) and their role in affecting the T. pityocampa density. Studies on nests of the pine processionary caterpillar were carried out in 2022 in two forest sites, namely Ghilas and El-Mroudj (NW Algeria). The mean (±SD) density of winter nests was higher in the cedar forest of El-Mroudj (1.22±0.26) than the Aleppo pine forest of Ghilas (1.62±0.60). The nest density differed with topographic orientation (F: 96.66, p<0.001). The nests of T. pityocampa caterpillars were directed mostly in the south side (the sunny part) of host trees, accounting for 48.5% and 43.5% of the total number of nests in El-Mroudj and Ghilas, respectively. At both sites, larval nest height was positively correlated with tree height (n = 126, P<0.001).